EMANSIPASI DAN HUMANISASI PENDIDIKAN KARTINI DI ERA KECERDASAN BUATAN - Rumahorbo, Rosmawaty; Kuswandi, Dedi; Wedi, Agus (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Digital access inequality and the risk of dehumanization resulting from the integration of artificial intelligence (AI) demand a re-evaluation of the increasingly mechanistic orientation of modern education. This study aims to revitalize R.A. Kartini's educational values ??to formulate an ethical framework for inclusive and humanist education relevant to the challenges of the technological era. Through a qualitative approach with a historical-conceptual analysis design and a literature review of primary documents and recent global reports, this study examines the transformation of Kartini's thinking. Key findings indicate that Kartini's principle of freedom of thought serves as an antithesis to algorithmic bias, while her vision of humanization reinforces the urgency of authentic pedagogical relationships threatened by automation. This study also formulates the concept of